2021
DOI: 10.1017/ice.2021.159
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of surgical site infections following total hip replacement and total knee replacement surgeries identified by Infection Prevention and Control and the National Surgical Quality Improvement Program in Alberta, Canada

Abstract: Objective: To understand how the different data collections methods of the Alberta Health Services Infection Prevention and Control Program (IPC) and the National Surgical Quality Improvement Program (NSQIP) are affecting reported rates of surgical site infections (SSIs) following total hip replacements (THRs) and total knee replacements (TKRs). Design: Retrospective cohort study. Setting: Four hospitals in Alberta, Canada. Patients: Those with THR or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…While our study’s TKA and THA rates were slightly lower than the CDC and ECDC reported rates [ 2 , 24 , 25 ]. This finding is consistent with previously published studies [ 26 ]. The observed decrease in the incidence of SSIs throughout the study period might have resulted from uniform provincial surveillance initiated by the Alberta Health Services IPC program starting in March 2012 [ 27 ].…”
Section: Discussionsupporting
confidence: 94%
“…While our study’s TKA and THA rates were slightly lower than the CDC and ECDC reported rates [ 2 , 24 , 25 ]. This finding is consistent with previously published studies [ 26 ]. The observed decrease in the incidence of SSIs throughout the study period might have resulted from uniform provincial surveillance initiated by the Alberta Health Services IPC program starting in March 2012 [ 27 ].…”
Section: Discussionsupporting
confidence: 94%
“…At present, the theory of protective motivation is mainly used in the prediction and intervention of health behavior, and it has also been widely used in the selfmanagement of chronic diseases. Domestic studies have applied this theory to chronic diseases and achieved good results [8]. Based on this, this study focuses on the effect of the protective motivation intervention nursing model on the functional recovery of patients after hip arthroplasty and its clinical significance.…”
Section: Introductionmentioning
confidence: 99%
“…Despite detailed instructions provided by the NHSN, concerns regarding subjective application of definitions have been raised and discrepancies have been noted when comparing NHSN outcomes to other surveillance initiatives, notably the American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP). 15,36,37 Benefits of automation: Speed, accuracy, and efficiency Despite the requirement for chart review to apply the NHSN definition for device-associated infections and SSIs, automating aspects of surveillance can, through extraction of the available electronic elements, restrict the possible HAI cases that require chart review to only those that would otherwise meet the NHSN definition. In the CAUTI example, by applying elements 1 and 3, an automated system limits the total cases that require chart review.…”
Section: Ssimentioning
confidence: 99%